SCOPE OF BUSINESS FOR SHARIA FINANCING INSTITUTIONS - Sri Mulyati; Mukhtar Lutfi (Cross-Border Journal of Business Management, 2023)
At present, sharia financing is very much needed by the Muslim community in order to support economic activities, especially businesses that are carried out in need of additional riba-free capital. This study aims to describe the meaning of Islamic financing institutions and their scope of business. This research belongs to the type of qualitative research with a library research approach in which literature or documents are the main data. Based on this study, it can be concluded that finance companies are business entities outside of banks and non-bank financial institutions specifically established to carry out activities that are included in the business sector of financing institutions. The business activities of financing institutions are leasing, factoring, credit card business, and consumer financing.